2011
DOI: 10.1007/s00702-011-0729-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies 5q21 and 9p24.1 (KDM4C) loci associated with alcohol withdrawal symptoms

Abstract: Several genome-wide association (GWA) studies of alcohol dependence (AD) and alcohol-related phenotypes have been conducted; however, little is known about genetic variants influencing alcohol withdrawal symptoms (AWS). We conducted the first GWA study of AWS using 461 cases of AD with AWS and 408 controls in Caucasian population in the Collaborative Study on the Genetics of Alcoholism (COGA) sample. Logistic regression analysis of AWS as a binary trait, adjusted for age and sex, was performed using PLINK. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…For example, histone H3 lysine 9 dimethylation and trimethylation (H3K9me2/3) and H3K27me3 are considered repressive marks to transcription, while H3K4me2/3 is considered a mark of actively transcribed chromatin (Kouzarides, 2007; Krishnan et al, 2014). Interestingly, genome-wide association studies (GWAS) have identified the genomic region encompassing the histone demethylase KDM4C gene as a hotspot associated with alcohol withdrawal symptoms (Wang et al, 2012). As research into the negative affective states seen during alcohol withdrawal and addiction continues, additional epigenetic modifications such as histone methylation, phosphorylation, and others may emerge as novel biomarkers of alcohol-induced anxiety in brain circuits such as the amygdala (Krishnan et al, 2014; Berkel and Pandey, 2017).…”
Section: Chronic Alcohol Exposure-induced Withdrawal Is Anxiogenicmentioning
confidence: 99%
“…For example, histone H3 lysine 9 dimethylation and trimethylation (H3K9me2/3) and H3K27me3 are considered repressive marks to transcription, while H3K4me2/3 is considered a mark of actively transcribed chromatin (Kouzarides, 2007; Krishnan et al, 2014). Interestingly, genome-wide association studies (GWAS) have identified the genomic region encompassing the histone demethylase KDM4C gene as a hotspot associated with alcohol withdrawal symptoms (Wang et al, 2012). As research into the negative affective states seen during alcohol withdrawal and addiction continues, additional epigenetic modifications such as histone methylation, phosphorylation, and others may emerge as novel biomarkers of alcohol-induced anxiety in brain circuits such as the amygdala (Krishnan et al, 2014; Berkel and Pandey, 2017).…”
Section: Chronic Alcohol Exposure-induced Withdrawal Is Anxiogenicmentioning
confidence: 99%
“…Interestingly, a large number of causative genetic mutations have been found in genes encoding enzymes that catalyse the addition or removal of the trimethylation mark of Lys4 on H3 (H3K4me3) and H3K9me2 109, 110, 111115 (see the table). Histones at the promoter regions of transcriptionally active genes are marked with H3K4me3.…”
Section: Figurementioning
confidence: 99%
“…Histone methylation is a dynamic reversible process and is under the control of two opposing groups of enzymes-the lysine methyltransferases and the lysine demethylases (Kouzarides, 2007). Genome-wide association studies have found KDM4C (a lysine demethlyase of the jumonji domain 2 (JMJD2) family) loci associated with alcohol withdrawal (Wang, Liu, Zhang, Wu, & Zeng, 2012). Other drugs of abuse, such as cocaine, resulted in a reduction of G9a and G9a-like protein (GLP) (lysine dimethyltransferases), which corresponded to a decrease in H3K9me2, and an increase in spine density in the NAc and cocaine place preference, whereas overexpression was able to reverse these effects (Maze et al, 2010).…”
Section: Introductionmentioning
confidence: 99%